How Facial Expressions of Emotion Affect Distance Perception - Kim, Nam-Gyoon; Son, Heejung (Frontiers in Psychology, 2015)
Facial expressions of emotion are thought to convey expressers’ behavioral intentions, thus priming observers’ approach and avoidance tendencies appropriately. The present study examined whether detecting expressions of behavioral intent influence perceivers’ estimation of the expresser’s distance from them. Eighteen undergraduates (9 male and 9 female) participated in the study. Six facial expressions were chosen on the basis of degree of threat—anger, hate (threatening expressions), shame, surprise (neutral expressions), pleasure and joy (safe expressions). Each facial expression was presented on a tablet PC held by an assistant covered by a black drape who stood 1m, 2m, or 3m away from participants. Participants performed a visual matching task to report the perceived distance. Results showed that facial expression influenced distance estimation, with faces exhibiting threatening or safe expressions judged closer than those showing neutral expressions. Females’ judgments were more likely to be influenced; but these influences largely disappeared beyond the 2m distance. These results suggest that facial expressions of emotion (particularly threatening or safe emotions) influence others’ (especially females’) distance estimations but only within close proximity.